PENGEMBANGAN INSTRUMEN KOMPETENSI SOSIAL MAHASISWA CALON GURU - Suparji Suparji (Universitas Negeri Malang, 2016)
Developing Instruments to Measure the Social Competence of Teacher-candidates. This study aimed to produce a valid and reliable instrument to measure social competence of student teachers. The try-outs were carried out three times: preliminary field try-out conducted in four schools involving 12 student teachers, main field try-out in eight schools involving 100 student  teachers, and operational field try-out in 15 schools involving 200 student teachers. Data from the try-outs were analyzed using confirmatory factor analysis and descriptive analysis. The research findings indicated that the student teachers' social competence comprised three sub-competences, i.e. ability to cooperate, ability to communicate, and contribution to educational development. The results of the confirmatory factor analysis showed that the values of tobserved were all greater than 1.69 and the reliability index was 0.82. The result of the statistical modeling showed that the model was fit (χ2 = 1.44; p = 0.13212). The result of descriptive analysis showed that ability to cooperate, ability to communicate and contribution to educational development were all the acceptable factors to student teachers' social competence.   Pengembangan Instrumen Kompetensi Sosial Mahasiswa Calon Guru. Penelitian ini bertujuan untuk menghasilkan instrumen kompetensi sosial  mahasiswa calon guru yang valid dan reliabel. Uji coba dilakukan sebanyak tiga kali yaitu: ji coba awal pada empat sekolah dengan subjek coba 12 mahasiswa calon guru, uji coba lapangan utama pada delapan sekolah dengan subjek coba 100 mahasiswa, dan uji coba lapangan operasional pada 15 sekolah dengan subjek coba 200 mahasiswa. Analisis yang digunakan adalah analisis faktor konfirmatori dan analisis deskriptif. Hasil penelitian menunjukkan bahwa kompetensi sosial mahasiswa calon guru mencakup tiga indikator yaitu kemampuan bekerjasama, kemampuan berkomunikasi, dan kontribusi terhadap pengembangan pendidikan. Hasil analisis faktor konfirmatori menunjukkan bahwa semua nilai thitung>1,69 dan reliabilitasnya adalah 0,82. Statistik model yang dihasilkan menunjukkan model yang fit (χ2=1,44 p=0,13212). Hasil analisis deskriptif menunjukkan bahwa indikator kemampuan bekerjasama, kemampuan berkomunikasi, dan kontribusi terhadap pengembangan pendidikan berkategori baik.